DECENTRALIZATION AND ITS IMPACT ON PRIMARY EDUCATION OUTCOMES - Deniey Adi Purwanto (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
Development outcomes nowadays not only measured by the successful of economic growth but more comprehensively by the achievement of human development. Obviouslyeducation has been place a one substantial factor not only as a basic human right but also in international development. Meanwhile after more than 8 years of decentralization inIndonesia, many concerns arise regarding the decentralization impacts. One of the considerable questions is on how far the fiscal decentralization has enhanced education development achievement. Therefore, a set of fiscal decentralization variables used in this paper to analyze their roles on primary education outcomes. Enrollment Rate used as dependent variable to represent the primary education outcomes. Regional characteristics were also utilized to improve the robustness of the result.Using panel data set of 434 sub provincial regions (districts and cities) in Indonesia, the estimation result show that fiscal decentralization instrument played a significant roleon primary education outcomes. Furthermore, DAK seems to have a greater impact on primary education outcomes than DAU. Additionally the estimation result also shows thatthere is still a significant disparity among sub provincial region in primary education achievement. The results suggest that fiscal decentralization instrument rearrangement substantially needed next to the education development equalization in all sub provincial region. This way, decentralization will foster more favorable outcomes in education development outcomes hopefully.Keywords: decentralization, primary education, panel data.